038 Respiratory viral infections in Team Finland during 2019 Nordic World SKI Championships: a controlled study. (3rd March 2020) - Valtonen, Maarit; Gronroos, Wilma; Luoto, Raakel; Waris, Matti; Uhari, Matti; Heinonen, Olli; Ruuskanen, Olli
Abstract : Background: The occurrence, etiology and clinical presentation of respiratory viral infections in elite athletes is unclear. Design: A prospective controlled follow-up study. Objective: Do elite athletes have an increase in risk of acute respiratory viral illnesses? Setting: We followed respiratory viral infections in Team Finland during 2019 Nordic World Ski Championships and in sex and age-matched controls in Finland. Participants: 26 athletes, and 36 staff members. 52 control subjects were adjusted for age sex and number of children. Intervention: Nasal swabs were taken from team members on days 1, 7 and 13 during the Games which lasted 14 days. Respiratory symptoms were recorded daily. At the onset of a symptom two nasal swabs were taken. One swab was analysed within 60 minutes using a point-of-care test (POCT) for 15 viruses. The other swab was tested for 16 viruses in laboratory. Results: Respiratory viruses were detected in 35%, 36% and 25% of the athletes, the staff members and the controls, respectively. Ten out of 26 (38%) athletes and 6 out of 36 (17%) staff members and 3 out of 52 (6%) controls experienced symptoms of respiratory infection. Asymptomatic infections were identified in 4%, 19% and 21%, respectively. The etiology of respiratory infections was detected in 84% of the cases. Four virus clusters were identified caused by rhinovirus, coronavirus 229E and NL63 and respiratory syncytial virus B. The clinical presentation of the infections in athletes was mild and the median duration of symptoms was 5.5 days. One athlete lost a competition due to a viral respiratory infection. Conclusions: The athletes had a 6-fold increase in risk of illness compared to normally physically active controls. The athletes had significantly less asymptomatic infections compared to staff and controls. Despite the infection prevention protocols, viruses circulated actively within the team.